PENERTIBAN PEDAGANG KAKI LIMA DI PASAR BENGKAYANG - Sabinus Beni (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2022)
Street vendors are a classic problem that is always found in all parts of Indonesia, its existence always makes cities/markets less organized and causes traffic jams due to their operational activities. This research was conducted in Bengkayang City based on Regional Regulation number 10 of 2019 Bengkayang Regency concerning the Arrangement and Empowerment of Street Vendors to find out whether the control is in accordance with the Regional Regulation or not. The findings in this study suggest that the control/relocation implemented by the Bengkayang Regional Government by relocating to street vendors who sell vegetables is in accordance with the Regional Regulation and a market will be built to sell with a more modern and humanist concept for vegetable traders so that they can beautify the city. The recommendation for the Bengkayang Local Government is to immediately build a representative vegetable market that is easily accessible to all parties in order to create justice for vegetable traders who have been relocated to two different places